Assessing Security, Capacity and Reachability of a Heterogeneous Industrial Network during Planning Phase - Ray, Apala; Akerberg, Johan; Björkman, Mats; Gidlund, Mikael (EAI Endorsed Transactions on Security and Safety, 2016)
In an industrial plant, there is usually a mix of devices with diﬀerent levels of security features and computation capabilities. If a mix of devices with various degrees of security features and capabilities communicate, the overall network dynamics with respect to security and network performance will be complex. A secure communication path with high latency and low bandwidth may not satisfy the operational requirements in a plant. Therefore, there is a need to assess the relation of security and network performance for overall plant operation. In this work we focus on identifying an optimal ﬂow path between two devices in a multi-hop heterogeneous network. We propose a model and an algorithm to estimate and generate a network path identiﬁed by ﬂow performance indicators of a heterogeneous communication network. Through an example, we show how the ﬂow performance metrics change with security, capacity and reachability of the devices in the network.
Keywords: Security Modeling; Network Assessment; Routing; Path Planning